Rural Masonry Isolating Structure and LRB Experiment: Seismic Resistance Properties and Statistical Data Curve Analyses - Jiayao Zheng (Advances in Materials Science and Engineering)
The low masonry structure is the most commonly applied building type in rural China. It is possible to install small-diameter, low cost, and easily constructed laminated rubber bearing (LRB) components. Isolation technology has broad application prospects in rural buildings. We developed a small-diameter LRB in this study wherein the isolation layer is set above the floor for easy installation and replacement. We built and tested 4 walls to observe the effects of different LRB thicknesses; we assessed test respective phenomena and seismic parameters accordingly. We ran another test on five small-diameter LRB components with varying horizontal stiffness, different forms of shear strain-equivalent horizontal stiffness, and postyield stiffness while changing the fitting formula for the second shape coefficient to give small-diameter LRB design providing gist.